Rancang Bangun Aplikasi Ppic Dalam Manajemen Biaya Dan Waktu Proyek Sistem Informasi (Studi Kasus Stikom Surabaya) - Alex Slamet Suhamto; M. J. Dewiyani Sunarto; Tan Amelia (Jurnal Sistem Informasi Universitas Dinamika, 2012)
Management becomes indispensable in this era. Project management was one of that. In the knowledge area, project management can be divided into cost and time management. The goals of cost and time management are to produce a calculation of an effective estimated cost and efficient time management. This system was built to produce an effective cost estimate calculation based on Cost of Quality method and good time management based on Critical Path method. After the implementation and evaluation, the system has success to created project cost estimate and time management based on Cost of Quality and the Critical Path method. Keywords: Information System, Project Management, Cost of Quality, Critical Path